Factors contributing to communication skills development in cochlear implanted children - Ostojić, Sanja B; Djoković, Sanja; Radić-Šestić, Marina; Nikolić, Mina; Mikić, Branka; Mirić, Danica (Vojnosanitetski pregled, 2015)
Background/Aim. Over the last 10 years more than 300 persons received cochlear implant in Serbia and more than 90% of the recipients were children under 10 years of age. The program of cochlear implantation includes postoperative rehabilitation in which cognitive, integrative and developmental methods are used. The study was conducted to reveal factors affecting communication performance (CP) of cochlear implanted (CI) children. Special attention was focused on the influence of the duration and intensity of rehabilitation and hearing age on further development of communication skills. Methods. A group of 30 CI children (13 boys and 17 girls) aged 2 to 5 years was enrolled in the study. All of the children had average intelligence and no other developmental disorder. They lived in families and attended rehabilitative seances 3 to 5 times a week. Their parents/caregivers answered structured questionnaire about functioning after pediatric cochlear implantation (FAPCI) and the results were the subject of detailed statistical analysis. Results. Analysis of variance did not show any difference between the boys and the girls regarding FAPCI achievements (F (1, 28) = 2.909; p = 0.099) and age aberration in CP score (F (1, 28) = 0.114, p = 0.738). Correlation analysis showed a statistically significant difference in FAPCI scores related to hearing age and duration of rehabilitation. Regression analysis (enter method) showed that model consisting of indipendent variables significantly contributed to prediction of overall FAPCI scores and Adjusted R2 value could explain 32% difference in communication skills of participants in this study. Conclusion. Communication skills of CI children evaluated by FAPCI are falling behind normatives for normal hearing children 18.6 months on the average. Hearing age, duration and intensity of rehabilitation have positive predictive value for communication skills development. Later identification of hearing loss and later cochlear implantation lead to delayed development of communication skills.
Keywords: cochlear implants; child; communication; questionnaires